2019
DOI: 10.3390/sci1020033
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin Interacts and Co-Localizes with Components of Pre-Catalytic Spliceosome Complexes

Abstract: Nucleolin is an RNA binding protein that is involved in many post-transcriptional regulation steps of messenger RNAs in addition to its nucleolar role in ribosomal RNA transcription and assembly in pre-ribosomes. Acetylated nucleolin was found to be associated with nuclear speckles and to co-localize with the splicing factor SC35. Previous nuclear pull down of nucleolin identified several splicing components and factors involved in RNA polymerase II transcription associated with nucleolin. In this report, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
(94 reference statements)
1
2
0
Order By: Relevance
“…Therefore, its function is highly implicated in AS. NCL in the nuclear speckles colocalizes with SC35 (as we also observe in our study), and is reported to interact with the pre-catalytic spliceosome complex and regulate AS of fibronectin ( 80 ). NCL is also known to play a major role in splice site selection ( 81 ).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, its function is highly implicated in AS. NCL in the nuclear speckles colocalizes with SC35 (as we also observe in our study), and is reported to interact with the pre-catalytic spliceosome complex and regulate AS of fibronectin ( 80 ). NCL is also known to play a major role in splice site selection ( 81 ).…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have indicated a connection of NCL with splicing factors (44)(45)(46)(47). We have previously found NCL as an integral component of the endogenous spliceosome (supraspliceosome), where it was identified associated with specific supraspliceosomes at all splicing stages (33).…”
Section: Ncl -A Multifunction Protein With Novel Role In the Spliceosomementioning
confidence: 96%
“…It has been suggested that the transient interaction of nucleolin with the pre-rRNA during transcription might be involved in the correct folding of the long pre-RNA which is required for the processing in mature ribosomal RNA [13][14][15][16][17] but it remains to be demonstrated if the RNA binding specificity of nucleolin towards pre-rRNA is important as deletion of the RNA binding domains responsible for this specificity do not seems to be crucial for the vital function of nucleolin [7]. By analogy to this co-transcriptional role of nucleolin in pre-rRNA maturation and assembly with proteins, it has been recently suggested that acetylated nucleolin could also be involved in the assembly of pre-catalytic spliceosomes and in splicing reaction [18,19]. Several reports suggest also that nucleolin could be involved in the regulation of transcription of some ANP polymerase II genes [20][21][22][23][24].…”
Section: Nucleolin An Abundant Multifunctional Protein With Multiple Cellular Localizationmentioning
confidence: 99%